Comparative Analysis of Ritual in World Religions - Amadi, Emmanuel Echezolochin; Kii, Pius Barinaadaa (NIU Journal of Social Sciences; Vol 11 No 2 (2025): NIU Journal of Social Sciences, Vol. 11 No. 2, June 2025, 2025)
This essay examines the comparative analysis of ritual in world religions such as Christianity, Islam, Judaism and African traditional religion. Ritual is one essential element that cut across religions. Ritual like symbol, vary from one religion to another. In Christianity. Eucharist or Sacrament believed to be prominent is the re-enactment of the last supper Jesus had with His disciples before His arrest and crucifixion. In Islam, it is the Hajj , believed to be one of the most important rites Moslem pilgrims undertake in Mecca. In Judaism, it is the feast of Passover, also known as the feast of freedom; which symbolically reminds the Jewish people of how God delivered them from slavery in Egypt. Remarkable things about ritual in all these religions is that it is believed not only to be real but also make sense to the adherents of these religions. But of paramount importance of it all is that it creates an avenue for communion and communication between the adherents and the object of worship on one hand and among the worshippers on the other hand. The study relied more on secondary sources (published-materials). The study adopts phenomenological approach to describe and interpret the rituals relating to these religions. Findings reveal that ritual has helped to promote religious and social solidarity; enhance the integration of Christianity, Islam and Judaism respectively. Keywords: Religion, Ritual, Christianity, Islam and Judaism